2019
DOI: 10.1103/physrevb.99.174414
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field modelling of magnetic nanoparticles: The effect of particle size and shape on the Curie temperature

Abstract: A Heisenberg mean-field model is used to study the effect of size and shape on the Curie temperature of magnetic nanoparticles. Simple cubic, body-centered cubic, and magnetite nanoparticles are modelled as spheres, cubes, and needlelike particles. The Curie temperatures of particles of different shape, but with the same crystal structure and smallest dimension d, are found to differ. The range in the value of the Curie temperature between particles of different shape, T C , is found to be ∼20% of the bulk val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…We start with a nucleation diameter for magnetite of 2 nm (Baumgartner et al., 2013). For particles greater than a few nanometers, M s is independent of v (Penny et al., 2019). This is much below the blocking volume of the minerals of interest, therefore we assume M s to be independent of v .…”
Section: Methodsmentioning
confidence: 99%
“…We start with a nucleation diameter for magnetite of 2 nm (Baumgartner et al., 2013). For particles greater than a few nanometers, M s is independent of v (Penny et al., 2019). This is much below the blocking volume of the minerals of interest, therefore we assume M s to be independent of v .…”
Section: Methodsmentioning
confidence: 99%
“…Penny et al [20] have shown that a mean-field approach is valuable for the investigation of finite-size effects, including lattice types and particle shapes. To support the interpretation of our atomistic model calculation, we use a lattice site resolved Mean-field model outlined as follows [21].…”
Section: B Lattice Site Resolved Mean-field Modelmentioning
confidence: 99%
“…Penny et al [21] have shown that a mean-field approach is valuable for the investigation of finite-size effects, including lattice types and particle shapes. To support the interpretation of our atomistic model calculation, we use a lattice site resolved mean-field model outlined as follows [22].…”
Section: B Lattice Site Resolved Mean-field Modelmentioning
confidence: 99%